Probation practice in the information age - Phillips, Jake (Probation journal, 2017)
This article analyses the implications of the greater use of technology and information in probation practice. Using data generated via an ethnography of probation, the article firstly argues that probation in England and Wales now exists in what scholars would identify as ‘the information age’ (i.e. that computers and other technologies work to define and create probation practice as we know it). The article goes on to use actor-network theory to analyse two ‘heterogeneous networks’ to explore the way in which probation practitioners and the technologies they use interact to create particular forms of practice. The article argues that unless we understand the technology that underpins practice we cannot fully understand practice. Finally, the article considers the implications of this analysis for probation post-Transforming Rehabilitation (TR).